Bingkai Sara Dalam Berita Politik: Analisis Framing Berita Pengangkatan Prabowo Sebagai Menteri Pertahanan RI - Dzulfikar Ahmad (Jayapangus Press, 2021)
The sensitive issue of SARA is widely used in the political world. Both by politicians themselves and by the media. One of the uses of SARA issues in political news by the media is as a frame. Framing in political news has a negative tendency to overthrow a politician not far from the value of SARA as a minority. The framing of political news about SARA is examined in this study. This research examines the SARA frame in the news of Prabowo's appointment as the Indonesian defense minister. News that is the object of research are those published online by major media on their websites from 21 October 2019 to 27 October 2019. Namely since Prabowo was invited to the presidential palace until a week he served as the Indonesian defense minister. The research findings show that most of the news that is the object of the research has a Reject Prabowo frame.